Healthcare professionals and medical cannabis: a scoping review informed by the theoretical domains framework - O'Rourke, R.; Lima, M. L.; Jetten, J. (Journal of Public Health: From Theory to Pratice, 2022)
Aim: This scoping review aims to examine what determinants of behaviours, beyond knowledge, are used as per the theoretical domains framework (TDF) in relation to the research design and findings in the selected studies related to healthcare professionals and medical cannabis (MC). Subject and methods: The use of MC has been legalized in various countries and states over the last 10 years. This rapid change of a stigmatised ‘drug’ to a modern ‘medicine’ and contradictory laws have undermined the consistent implementation of MC in healthcare. Data synthesis of the evidence base in the selected studies used the TDF to examine the enablers and barriers influencing implementation of medical cannabis. The TDF was developed to support the implementation of change with healthcare professionals (Cane et al. Implement Sci 7:37, 2012). The TDF is comprised of 14 theoretical domains taken from 33 psychological change theories and 128 constructs. Results: Using the preferred reporting items for systematic reviews, 34 publications were identified that met the inclusion criteria. The domains most frequently identified as influencing behaviours were ‘knowledge’ and ‘beliefs about consequences’. Through a focus on knowledge in the studies, findings showed that improving education is required. However, multiple factors influencing behaviours of professional healthcare groups must also be considered to support consistent implementation of MC. Conclusion: Examining broader determinants of behaviour, beyond knowledge is required, such as environmental influences and the norms of healthcare professionals for consistent MC implementation. Use of the TDF to ensure multiple domains are included in future research and educative programs would support this aim.